2022
DOI: 10.1111/lam.13779
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ultraviolet, gamma- and X-ray irradiation on the growth, antibacterial activity and radio-protective of Lactobacillus rhamnosus

Abstract: Significance and Impact of the Study: Ionizing radiation is widely applied for food preservation and for correction of the gut microbiome of patients treated with radiation, rescuers, astronauts, etc. Some lactic acid bacteria (LAB) are of great potential in restoring the microbiome of patients, or in food biopreservation. This investigation revealed the radioresistance of Lactobacillus rhamnosus MDC 9661 with only some loss of antibacterial activity, maintaining other activities and the absence of an immunoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The microbiome balance can be disrupted by a number of factors, including diet, antibiotics, and other environmental factors. It was shown that the ionizing radiation can disturb the structure and function of the gut microbiome, leading to a range of health problems 20,21 . Ionizing radiation can damage the DNA of gut microbes, leading to pathological changes in their composition and activity.…”
Section: Introductionmentioning
confidence: 99%
“…The microbiome balance can be disrupted by a number of factors, including diet, antibiotics, and other environmental factors. It was shown that the ionizing radiation can disturb the structure and function of the gut microbiome, leading to a range of health problems 20,21 . Ionizing radiation can damage the DNA of gut microbes, leading to pathological changes in their composition and activity.…”
Section: Introductionmentioning
confidence: 99%